The Word of the Week – A dissemination project of pluricentric Hungarian - Váradi Krisztián; Вараді Крістіян; Lehocki-Samardžić Anna; Лехоцькі-Самарджич Анна (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2025)
Abstract. Hungarian is a pluricentric language, which means that it is used in public administration, education, culture, and other high-prestige linguistic domains in multiple countries. One of the main goals of the Termini Hungarian Language Research Network is to document the distinctive lexical elements of the regional language varieties spoken by Hungarian minorities outside the borders of Hungary and to establish these mostly state-language loanwords as recognized elements of the Hungarian lexicon. The Termini Online Hungarian Dictionary and Database (TOHDD), available online since 2007, contains more than 5,570 lexical borrowings from the everyday speech of Hungarian minorities living in Austria, Croatia, Romania, Serbia, Slovakia, Slovenia, and Ukraine. Promoting the content of the dictionary is a key task, as most people tend to have a negative attitude toward vocabulary elements that deviate from the standard variety of the Hungarian language. For this reason, a dissemination project showcasing cross-border language use has been launched under the name The Word of the Week. In 2016, the editors of the TOHDD in Croatia first introduced it as a column in a local newspaper. Shortly afterward, The Word of the Week posts began to appear on the Termini Facebook page, expanding to all regions. Every week, a loanword relevant to the given time period was shared via social media, allowing both Hungarians in Hungary and those living beyond the country’s borders to become familiar with the unique lexical elements of various regional language varieties. After a long pause, The Word of the Week resumed in April 2024 on a weekly basis and has yielded numerous positive results within a year. The posts have reached tens of thousands of people, who have liked, shared, or commented on the images more than 4,000 times, contributing to the greater acceptance of Hungarian language varieties spoken outside Hungary. The initiative has successfully ensured that discussions about different Hungarian language varieties are not confined to sociolinguistic and contact linguistic studies published in scientific journals but are also present in a widely accessible and frequently used social media platform.

Резюме. Угорська мова є плюрицентричною, оскільки спостерігаємо її використання в державному управлінні, освіті, культурі та в інших престижних сферах мовлення в кількох країнах. Однією з основних цілей Дослідницької мережі з вивчення угорської мови «Termini» є документування характерних лексичних елементів регіональних мовних варіантів, якими послуговуються угорські меншини за межами Угорщини, та визнання цих здебільшого запозичених з державних мов слів як частини угорського лексикону. Угорсько–угорський словник і база даних «Termini», доступні онлайн з 2007 року, містять понад 5570 лексичних запозичень із повсякденного мовлення угорських меншин, що проживають в Австрії, Хорватії, Румунії, Сербії, Словаччині, Словенії та Україні. Популяризація цього словника є важливим завданням, оскільки більшість людей сприймають лексику, яка відхиляється від стандартної угорської мови, у негативному світлі. Саме тому було започатковано інформаційний проєкт, що демонструє мовне різноманіття угорців за кордоном, під назвою «Слово тижня». У 2016 році редактори словника «Termini» в Хорватії вперше представили цей проєкт як рубрику в місцевій газеті. Незабаром після цього публікації «Слово тижня» почали з’являтися на сторінці «Termini» у Facebook, охоплюючи всі регіони. Щотижня через соціальні мережі публікувалося запозичене слово, актуальне для відповідного періоду, що дає змогу як угорцям в Угорщині, так і тим, хто живе за її межами, ознайомитися з унікальними лексичними елементами різних регіональних мовних варіантів. Після тривалої перерви «Слово тижня» відновилося у квітні 2024 року, публікувалося щотижня й протягом року принесло численні позитивні результати. Публікації переглянули десятки тисяч людей, які вподобали, поширили чи прокоментували зображення понад 4000 разів, сприяючи ширшому визнанню мовних варіантів угорської мови, що використовуються за межами Угорщини. Завдяки цій ініціативі обговорення різних угорських мовних варіантів більше не обмежується лише соціолінгвістичними та контактнолінгвістичними дослідженнями в академічних журналах, а стало доступним на соціальній платформі, що широко використовується.

A magyar egy pluricentrikus nyelv, mivel egyszerre több országban is használják a közigazgatásban, az oktatásban, a kultúrában, és egyéb magas presztízsű nyelvhasználati színtereken. A Termini Magyar Nyelvi Kutatóhálózat egyik fő célja, hogy a Magyarország határain túl élő magyar kisebbségek regionális nyelvváltozatainak sajátos lexikális elemeit adatolja, valamint ezeket a nagyrészt államnyelvi kölcsönszavakat a magyar szókészlet elemeiként ismertesse el. Ezt a célt szolgálja a 2007 óta az interneten is elérhető Termini magyar–magyar szótár és adatbázis, amely az Ausztriában, Horvátországban, Romániában, Szerbiában, Szlovákiában, Szlovéniában és Ukrajnában élő magyar kisebbségek lexikai kölcsönzéseit tartalmazza, szám szerint több mint 5570 darabot. A szótár tartalmának népszerűsítése kiemelt feladatnak számít, hiszen a sztenderdtől eltérő szókészleti elemekhez a legtöbben negatívan viszonyulnak. A regionális nyelvváltozatokhoz fűződő attitűdök javítása érdekében a Termini nyelvészei létrehozták A hét szava elnevezésű, határon túli nyelvhasználatot szemléltető disszeminációs projektet. 2016-ban a Termini-szótár horvátországi szerkesztői indították útjára a rovatot egy helyi napilapban, majd rövidesen minden régióra kiterjesztve a Termini Facebook-oldalán kezdtek megjelenni A hét szava-bejegyzések. Minden héten egy, az adott időszakra nézve releváns kölcsönszó került megosztásra a közösségimédia-platformon keresztül, így a magyarországi és az országhatáron túli magyarok egyaránt megismerkedhettek az egyes regionális nyelvváltozatok sajátos lexikai elemeivel. Néhány év szünet után A hét szava 2024 áprilisától indult el újra heti rendszerességgel, és egy év alatt számos pozitív eredményt hozott. Emberek tízezreit sikerült elérni a bejegyzésekkel, akik több, mint 4000 alkalommal kedvelték, osztották meg vagy kommentálták a képeket, ezzel hozzájárulva a magyar nyelv határon túli változatainak nagyobb mértékű elfogadottságához. Sikerült azt elérni, hogy ne csak tudományos folyóiratokban megjelenő szociodialektológiai és kontaktológiai tanulmányokban legyen szó az egyes magyar nyelvváltozatokról, hanem a szélesebb közönség által gyakran látogatott és használt közösségi médiában is.
A hét szava – A pluricentrikus magyar nyelv disszeminációs projektje
Слово тижня – Проєкт поширення плюрицентричної угорської мови
https://aab-philologica.kmf.uz.ua/aabp
Keywords: social media; lexical borrowings; Hungarian dialects; linguistic debordering; Termini Online Hungarian Dictionary and Database